Purinergic signaling displays a pro-inflammatory profile in lymphoid immune organs of Oreochromis niloticus experimentally infected by Providencia rettgeri: The role of pathophysiology - Baldissera M.D. (2019)
© 2019 Elsevier B.V.The pathophysiological mechanisms associated with immune responses to the opportunistic bacterial pathogen Providencia rettgeri in fish species are unknown. The aim of this study was to evaluate whether purinergic signaling generates anti-inflammatory or pro-inflammatory profiles in lymphoid immune organs of the Nile tilapia (Oreochromis niloticus) experimentally infected by P. rettgeri. Adenosine triphosphate (ATP) and adenosine diphosphate (ADP) hydrolysis activities in the spleen and triphosphate diphosphohydrolase (NTPDase) in the head kidney decreased in experimentally P. rettgeri-infected Nile tilapia on days seven and fourteen post-infection (PI) compared to the control group. At these same time points, splenic and head kidney adenosine deaminase (ADA) activity, and levels of ATP, interleukin-15 (IL-15) and metabolites of nitric oxide (NOx) increased in infected animals compared to their respective control groups; this was also observed for serum ATP levels. No significant difference was observed between groups regarding 5′-nucleotidase activity. These results suggest that purinergic signaling in lymphoid immune organs of Nile tilapia exerts a pro-inflammatory profile in response to P. rettgeri infection. This response contributes to the inhibition of immune and inflammatory responses by reduction of ATP hydrolysis and augmentation of ATP in the extracellular environment as well as augmentation in adenosine deamination and its possible reduction in the extracellular environment, leading to a self-sustained pro-inflammatory cycle, corroborated by excessive content of ATP (extracellular milieu), IL-15 and NOx levels. Purinergic signaling may thereby contribute to the pathophysiology of P. rettgeri infection.